Evaluation of soil fertility status of fruit orchards of Gilgit district, Gilgit Baltistan - Aman, Ali; Hassan, Javaid; Ijaz, Shahzada Sohail; Zaman, Anwar; Waqas, Muhammad (Journal of Pure and Applied Agriculture, 2023)
The productivity of fruit trees orchards mainly relies on soil fertility and nutrient requirements. For best growth and production, essential nutrients are required optimally. To restore productivity soil characteristics and nutrient status of orchards must be determined. A multi locational orchards survey was conducted to assess the nutrient status (apple, almonds, walnut, fig, lokad, permission and stone fruits) of fruit orchards in district Gilgit, Pakistan. Samples were collected from the canopy area of the fruit trees at depth, viz, 0-20 cm using a stainless auger and analyzed for pH, EC, soil texture, organic matter, available phosphorus and potassium, AB-DTPA micronutrients. Results showed soil texture varied from sandy loam to silt loam. 56 % of samples were sandy loam with slightly neutral to alkaline pH. Non-saline soils having medium to high organic matter, Phosphorus levels varied from 0.57 to 39.7 mg kg-1, and total nitrogen was inadequate in 60% of the soil samples, however adequate K was found due to K bearing minerals. Soil micronutrient (Cu, Fe, and Mn) except Zn was sufficient in all fruit’s orchards. 77 % of samples were low in Zn content where 4% of samples were in marginal range and 19% of samples were in the adequate range. Most of the fruit’s orchards were low in Zn and total nitrogen. The chemical soil conditions in fruit orchards are often poor, emphasizing that integrated nutrient management through fertilization regulation and soil property monitoring is essential for long-term fruit production in Gilgit district.